Socio-demographic factors and knowledge as correlates of family caregiving ability in schizophrenia with risk of violence: A cross-sectional study - Ristiana, Risti; Sumartyawati, Ni Made; Santosa, I Made Eka; Darthayasa, I Nengah (Yayasan Pendidikan Kardin Assidiq, 2025)
Background: Caregiving for individuals with schizophrenia, particularly those at an elevated risk of exhibiting violent behavior, presents significant challenges for family members, especially in regions with limited resources. It is essential to understand the factors that influence caregivers' competence to ensure effective home management and mitigate the risk of violent incidents. Objective: The purpose of this study was to investigate the relationship between socio-demographic factors such as age, occupation, and education, and the knowledge and capabilities of family caregivers in managing schizophrenia patients at risk for violence. Method: A quantitative cross-sectional study was conducted at Mutiara Sukma Mental Hospital in West Nusa Tenggara, involving eighty-nine family caregivers recruited through accidental sampling. Data were gathered using validated questionnaires designed to assess demographic information, knowledge regarding schizophrenia, and caregiving efficacy. Bivariate analysis was performed using the Chi-Square test, with a significance threshold set at p < 0.01. Results: The majority of participants were in early adulthood (50.6%) and were employed (57.3%). The statistical analysis uncovered significant correlations between age, occupation, education, knowledge, and the caregivers' competencies in providing care (p < 0.01). Caregivers with higher educational attainment and substantial knowledge demonstrated enhanced abilities in managing medication and addressing violent behaviors compared to those with lower educational levels or insufficient understanding of the condition. Conclusion: Socio-demographic factors and health literacy play crucial roles in determining caregiving abilities. It is recommended that nursing interventions prioritize targeted psychoeducation and social support tailored for families encountering educational and socioeconomic challenges, thereby enhancing patient safety and the overall quality of care in home settings.